SUKU AS SELF-REPRESENTATION FOR THE ADAT PERPATIH COMMUNITY IN NEGERI SEMBILAN, MALAYSIA - AW Radzuan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This article considers the importance of suku (clan) for the adat perpatih community in Negeri Sembilan. Generally, Malays in Negeri Sembilan practise adat perpatih as part of their customary law, with suku being one of the fundamental principles with which its contemporary members identify. Without suku, adat perpatih could not continue to exist. However, suku has increasingly been practised less by adat perpatih community members due to their preferences changing over time. Accordingly, this study examined the importance of suku for members of the adat perpatih community in Negeri Sembilan, especially the impact of suku on their life. Twelve research participants participated in the study, which involved in-depth interviews and participant observations. This revealed 12 different suku divisions, with the practice of suku generally found to enable recognition of community, the representation of identity, a sense of belonging, and an act of protection and security.